Historical Phase of the Development of Indonesia Islamic Education - Lulu Nur Lathiifah Jamiilah (Social Impact Journal, 2023)
This article aims to describe the history of the development of Islamic education in Indonesia, both during the colonial period, Dutch colonialism, and up to the Japanese colonial period. The method used in this paper uses literature study, by collecting material from various references, including journal articles, books, and other historical records that are closely related to Islamic education in Indonesia. The results of the discussion in this article are that the historical development of Islamic education in Indonesia has faced quite a long dynamic with various problems and challenges faced by national figures, to create sovereign Indonesian education in the midst of changes over time, both during the kingdom, Dutch colonialism, and Japanese colonialism.